Desain Sistem Pakar Monitoring Perkembangan Balita - Didik Nugroho Bebas Widada (STMIK Sinar Nusantara, 2011)
Expert system is a software that can replace an individual's expertise in aparticular field. Expert systems can be developed to overcome the limitations of the number of experts in aspecific field. In addition to the expert system canused to disseminate information on a particular field. As health expert system scan be used to disseminate information or knowledge development to young couples. Research methods of observation and inference engines use the backward Chaining . The purpose of the research result in infant growth monitoring expert system. Key word : Expert system,software,dissemination information, Young Couples.